2014
DOI: 10.1364/ao.53.001674
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical security system based on a joint transform correlator in the Fresnel domain

Abstract: A new optical security system for image encryption based on a nonlinear joint transform correlator (JTC) in the Fresnel domain (FrD) is proposed. The proposal of the encryption process is a lensless optical system that produces a real encrypted image and is a simplified version of some previous JTC-based encryption systems. We use a random complex mask as the key in the nonlinear system for the purpose of increasing the security of the encrypted image. In order to retrieve the primary image in the decryption p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 40 publications
1
72
0
2
Order By: Relevance
“…Finally, we propose some guidelines in order to increase the security of the JTCbased encryption system against the CPA [26], and KPA [27]. The nonlinear operation introduced in the JFPS already improves the security of the encryption system against the CPA, just as it was proved in [14,16]. To increase the security of the encryption system against KPA, we recommend to use different probability density functions (not only the uniform distribution) for the random code functions corresponding to the RPM h(x) [14,16].…”
Section: Approach Ii: Removing the Zero-order Fractional Power Spectrmentioning
confidence: 94%
See 1 more Smart Citation
“…Finally, we propose some guidelines in order to increase the security of the JTCbased encryption system against the CPA [26], and KPA [27]. The nonlinear operation introduced in the JFPS already improves the security of the encryption system against the CPA, just as it was proved in [14,16]. To increase the security of the encryption system against KPA, we recommend to use different probability density functions (not only the uniform distribution) for the random code functions corresponding to the RPM h(x) [14,16].…”
Section: Approach Ii: Removing the Zero-order Fractional Power Spectrmentioning
confidence: 94%
“…To increase the security of the encryption system against KPA, we recommend to use different probability density functions (not only the uniform distribution) for the random code functions corresponding to the RPM h(x) [14,16]. A random complex mask (RCM) was utilized as key for the encryptiondecryption system presented in [16]. This RCM can be used to further improve the resistance of the JTC-based encryption in the FrFD against KPA [16].…”
Section: Approach Ii: Removing the Zero-order Fractional Power Spectrmentioning
confidence: 99%
“…From these pieces of information the attacker may recover crucial information of the security system such as the hidden decryption key. For the interested reader, the security flaws of the DRPE are analysed elsewhere ( [15][16][17] for a 4 f -processor, [39][40][13][14] for the JTC architecture).…”
Section: Moea [1] and The Newly Proposed Phc-moea Systems Against Twomentioning
confidence: 99%
“…Most of the optical security systems usually deal with a single primary image (for instance, an object, a plaintext, a signature, a biometric signal) as authenticator [2][3][4][5][6][7][10][11][12][13][14][18][19][20][21][22][23]. Some approaches permit to store multiple primary images, either in an optical memory [9] or in a single encrypted distribution [24][25][26][27], with the purpose of sequential and independent one-by-one decryption.…”
Section: Introductionmentioning
confidence: 99%
“…This is done by setting two random phase masks in the input and the Fourier planes. Since the publication of this method, the DRPE scheme has been applied in different domains, such as fractional Fourier transform (FRT) 9,10 , Fresnel transform (FrT) 11,12,13 , gyrator transform (GT) 14,15 , quaternion Fourier transform 16 , diffractive imaging 17 , dual fractional Fourier-wavelet 18 , fractional Mellin 19 , and Hartley transform 20 . Nevertheless, it has been demonstrated that DRPE scheme is vulnerable to some type of attacks 21,22,23 and due to its high shift sensitivity, it requires high alignment accuracy in the spatial domain systems.…”
Section: Introductionmentioning
confidence: 99%